Vibration Quantity Share of Multiple Faults with Similar Frequency Spectrum Characteristics in Rotational Machinery - Nezirić, Emir; Isić, Safet; Karabegović, Isak (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2022)
Characteristics of the vibrations of rotational systems with misalignment and rotating looseness are well known and they are used for fault detection in the rotating machinery. For the better understanding and easier decision make in the fault removing process it is necessary to know how severe each fault is. Lack of procedures for quantification of this faults in rotational machinery is evident. In this paper is investigated the possibility for use of multiple regression analysis for determination of quantity of faults in vibration velocity signal. An experimental motor – coupling – rotor system is created and produced. These systems have capability of changing the values of misalignment and rotational looseness. Measurement of vibrational quantities were conducted on these systems by using piezoelectrical accelerometers for different combinations of fault values. All measurements were stored and processed digitally. All measurements have shown the presence of the main characteristics of introduced faults. It is confirmed that it is not possible to use RMS (root mean square) of vibration velocity, since there is a lot of other factors which has significant impact on the vibration quantity.